Polymerase synthesis of photocaged DNA resistant against cleavage by restriction endonucleases - Vaníková, Zuzana; Hocek, Michal (Angewandte Chemie (International ed. in English), 2014)
5-[(2-Nitrobenzyl)oxymethyl]-2'-deoxyuridine 5'-O-triphosphate was used for polymerase (primer extension or PCR) synthesis of photocaged DNA that is resistant to the cleavage by restriction endonucleases. Photodeprotection of the caged DNA released 5-hydroxymethyluracil-modified nucleic acids, which were fully recognized and cleaved by restriction enzymes.
Keywords: pentoxyl; Ultraviolet Rays; DNA-Directed DNA Polymerase; DNA; ultrafialové záření; protective groups; photocaging; Pentoxyl; nucleotides; DNA Restriction Enzymes; DNA-dependentní DNA-polymerasy; restrikční enzymy; DNA polymerase